2005
DOI: 10.1007/b106365
|View full text |Cite
|
Sign up to set email alerts
|

The biosynthesis and functional roles of methylated nucleosides in eukaryotic mRNA

Abstract: Modified nucleosides are present in mRNA of all eukaryotes, albeit at much lower levels than in other RNA moieties such as rRNA, tRNA, and snRNA. Modification by methylation occurs on the terminal guanosine of the cap (N 7 -methylguanosine), and the first two encoded nucleosides (2'-O-methylnuculeosides) in most higher eukaryotes. Additional modifications of cap nucleosides occur in special cases where the cap is derived by trans-splicing in nematodes and kinetoplastids. Modification by methylation also occurs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
89
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(94 citation statements)
references
References 119 publications
(98 reference statements)
5
89
0
Order By: Relevance
“…(B) WT and hpm1⌬ mutant cells containing the plasmids described in panel A were labeled in vivo with [ 3 H]AdoMet as described in Materials and Methods, except that 3.5 OD 600 units of cells was labeled for 1 h. Total lysates were prepared in buffer C and acid hydrolyzed for amino acid analysis as described in Materials and Methods, except that the column was kept at 35°C and that 900 l of each fraction was taken for radioactivity determination. 3 H radioactivity is shown in counts per minute, and ninhydrin absorbance of the 3-methylhistidine standard was measured. (C) Quantification of polysome profiles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(B) WT and hpm1⌬ mutant cells containing the plasmids described in panel A were labeled in vivo with [ 3 H]AdoMet as described in Materials and Methods, except that 3.5 OD 600 units of cells was labeled for 1 h. Total lysates were prepared in buffer C and acid hydrolyzed for amino acid analysis as described in Materials and Methods, except that the column was kept at 35°C and that 900 l of each fraction was taken for radioactivity determination. 3 H radioactivity is shown in counts per minute, and ninhydrin absorbance of the 3-methylhistidine standard was measured. (C) Quantification of polysome profiles.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most common modifications is the addition of methyl groups to rRNA, tRNA, mRNA, snRNA, translation factors, and ribosomal proteins (1)(2)(3)(4). These reactions are catalyzed by the members of several families of structurally related methyltransferases that use S-adenosylmethionine as a methyl donor; some 1% of the genes in a variety of organisms encode such enzymes (5).…”
mentioning
confidence: 99%
“…RNA modifications generally fine-tune RNA structure and molecular interactions, and their detailed biological roles are under intense investigation (Grosjean 2005). N 6 -methyladenosine is the most abundant RNA modification in mammalian mRNA and long noncoding RNA (lncRNA), occurring on average in three to five sites per transcript (Bokar 2005). m 6 A modification pattern is highly dependent on cell types and conditions (Dominissini et al 2012;Meyer et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Two recently discovered m 6 A-demethylases are associated with obesity/diabetes and sperm development, indicating that the dynamics of m 6 A modification is biologically important (Jia et al 2011;Zheng et al 2012). Proposed m 6 A functions include mRNA splicing, export, stability, and immune tolerance (Bokar 2005;Karikó et al 2005), but m 6 A studies in mRNA/lncRNA were hindered by the lack of methods for its precise identification.…”
Section: Introductionmentioning
confidence: 99%
“…Establishing a physiological role for m6A will likely require employing a similar strategy involving point mutations in vivo at modified sites, nowadays made easier through the advent of CRISPR/Cas9 technologies (Cong et al 2013;Mali et al 2013). A potentially complicating factor is that it was found that point mutating an m6A site in vitro might result in accumulation of m6A at adjacent positions (Narayan et al 1994;Bokar 2005). However, more recent work pointmutating eight methylation sites in yeast found no support for accumulation of m6A at adjacent positions in vivo, suggesting that this is a viable strategy ).…”
mentioning
confidence: 99%